A YouTube Channel as a Support Tool in a Physics Course in Distance Education - Arguedas Matarrita, Carlos (2018)
This article describes a study that enabled the implementation of a YouTube channel as a technologicaltool to support a Physics I course for the teaching of natural science program at Universidad Estatal a Distancia of Costa Rica. The potential impact of such a technological tool in the teaching of natural science program was studied. Based on the results, the channel was designed with some videos exclusively made to support the topics within this course. YouTube was chosen because it offers advantages in terms of usability, accessibility, and ubiquity which are essential issues in distance education. Up to this moment, the channel has achieved its goal since it has a considerable number of visits.